Structural features and development of an assay platform of the parasite target deoxyhypusine synthase of brugia malayi and leishmania major - Silva, Suélen Fernandes [UNESP]; Klippel, Angélica Hollunder [UNESP]; Ramos, Priscila Zonzini; Santiago, André da Silva; Valentini, Sandro Roberto [UNESP]; Bengtson, Mario Henrique; Massirer, Katlin Brauer; Bilsland, Elizabeth; Couñago, Rafael Miguez; Zanelli, Cleslei Fernando [UNESP] (Public Library of Science (PLoS), 2020)
Deoxyhypusine synthase (DHS) catalyzes the first step of the post-translational modification of eukaryotic translation factor 5A (eIF5A), which is the only known protein containing the amino acid hypusine. Both proteins are essential for eukaryotic cell viability, and DHS has been suggested as a good candidate target for small molecule-based therapies against eukaryotic pathogens. In this work, we focused on the DHS enzymes from Brugia malayi and Leishmania major, the causative agents of lymphatic filariasis and cutaneous leishmani-asis, respectively. To enable B. malayi (Bm)DHS for future target-based drug discovery pro-grams, we determined its crystal structure bound to cofactor NAD+. We also reported an in vitro biochemical assay for this enzyme that is amenable to a high-throughput screening for-mat. The L. major genome encodes two DHS paralogs, and attempts to produce them recombinantly in bacterial cells were not successful. Nevertheless, we showed that ectopic expression of both LmDHS paralogs can rescue yeast cells lacking the endogenous DHS-encoding gene (dys1). Thus, functionally complemented dys1Δ yeast mutants can be used to screen for new inhibitors of the L. major enzyme. We used the known human DHS inhibi-tor GC7 to validate both in vitro and yeast-based DHS assays. Our results show that BmDHS is a homotetrameric enzyme that shares many features with its human homologue, whereas LmDHS paralogs are likely to form a heterotetrameric complex and have a distinct regulatory mechanism. We expect our work to facilitate the identification and development of new DHS inhibitors that can be used to validate these enzymes as vulnerable targets for therapeutic interventions against B. malayi and L. major infections.